Ayurveda Management of Attention-Deficit Hyperactivity Disorder: A Systematic Review - Weerasinghe, H.P.B.R.; Weerakoon, W.A.S.S. (Faculty of Indigenous Medicine, University of Colombo, 2025)
Attention Deficit Hyperactivity Disorder (ADHD) is characterized by inattention, hyperactivity, and impulsivity due to cognitive distortions (Vibhrama) affecting the mind and intellect, Ayurveda emphasizes therapies which balance brain doshas (Prana vata, Tarpaka kapha, Sadhaka pitta) using Ayurvedic medications. This study aimed to review Ayurveda management of attention deficit hyperactivity disorder in children through a systematic review. The systematic review utilized databases like Google Scholar, PubMed, ResearchGate, ScienceDirect, and AYUSH research portal databases between January 2014 to June 2024. Articles were screened using eligibility criteria and assessed for quality using the Jadad score, focusing on randomization, double blinding, and withdrawals. A total of 231 records were screened, with 8 studies selected for further analysis. The Jadad score was applied to these randomized clinical trials, revealing one study with a score of 5, two with 3, three with 2, one with 1, and one with 0. Three studies achieved the maximum possible Jadad score. The case study involved a six-year-old boy with combined-type attention deficit hyperactivity disorder, diagnosed using DSM-5 criteria and underwent internal and external Ayurvedic treatments. Clinical symptomatology was scored on a four-point scale. Before treatment, the child exhibited 64.70% of symptoms. After treatment, symptoms reduced to 29.41%, indicating a "Markedly improved" status. The study identified internal and external Ayurvedic treatment modalities including Medhya rasayana and panchakarma therapies offer effective management by balancing the doshas and improving cognitive functions and behavioral changes. Challenges such as small sample size limited clinical trials, and lack of comparative trials against placebo or conventional treatments highlight the need for further research.
Keywords: ADHD; Inattention; Hyperactivity and Impulsivity; Ayurvedic management; Unmada